A communication universe : manifestations of meaning, stagings of significance - Klyukanov, Igor (Lexington studies in political communication., 2010)
A Communication Universe: Manifestations of Meaning, Stagings of Significance presents a new theoretical understanding of communication. Igor E. Klyukanov conceptualizes the process of communication in terms of space and time, i.e., as a continuousprocess of meaningful spatiotemporal transformation. He goes on to examine four fundamental transformations and the four theoretical perspectives on the nature of communication. From the first perspective communication appears to be "pure space," then time comes into play more and more actively, and from the fourth perspective communication appears t.